Balé folclórico de Alagoas: 37 anos de história e os processos criativos na espetacularidade folclórica alagoana - Ayres, Francisco Rogers Cavalcanti (2014)
This paper reports the first time, all creative processes that enabled the creation and permanence of the Ballet Folklorico de Alagoas – Transart Group – the cultural scene of parafolclóricas dances of Alagoas, investigating its history and national history, educating youth and promoting our folk dances to a level of national and international visibility in these 37 years of activity.